Pesquisa docluster de imuno evasão e tipagem molecular em Staphylococcus aureus meticilina-sensíveis (MSSA), osolados de maipladores de alimentos - Baptistão, Lívia Gramolini [UNESP] (2014)
Staphylococcus aureus has various evasion mechanisms againt human innate immunity, many of them are carried by mobile elements enabling horizontal transfer of genes between strains, as with Immune Evasion Cluster (IEC) having great capacity for evasion and disease development which may vary from food poisoning to death for bacteremia when related to immuno compromised people, children and elderly. S. aureus is a frequent colonizer of skin and mucous membranes and can easily enter in food chain having hight transmissibility between people, animals and food which may be a problem when we think of evasion, adaptation ability and evolution. For these reasons the aim of this work was characterize S.aureus strains, isolated from hands and nare of food handlers, as to presence of IEC and molecular typing using spa-typing technique. We used 35 S. aureus strains and found the cluster types A, B, D e F, present in 10 isolates (28,5%). We found 15 different spa-types, being the most prevalent t127 and t002, besides a new spa-type described for the first time in this work, registered as t13335. The MSSA strains can be source of genes that contribute to meticillin resistant S. aureus virulence. Since frequency of IEC seems to be high in S. aures from human being and low is animal strains, may have occurred contamination of food handlers by foods of animal origin